ANALISIS KEPEMIMPINAN KEPALA DESA PEREMPUAN DALAM MENINGKATKAN PELAYANAN MASYARAKAT - Nursholikah, Istri (Jurnal Civic Hukum, 2016)
Leadership and human deifying two sides of the coin, who one another cannot beseparated, because basically human being born as the leader of the leadership. Leadership there are in all orgnisasai, from the level of most small and intimate, namely of a family until the village level, the city, the state, from the local level, regional and national, and international. Leadership village did not only occupied by men. With the advent of the times, now the position of women in the domain of political start to arise, especially for the village head. The arrival of the village head women certainly makes a fresh to women to actively involved in the domain of politica, but it a little bit too some the community to the eyes ofleadership the village head women. The problems to take is setting off from the responses the community with the absence of a head village women, methods and type leadership, with the constraints of faced and the solution offered. Data collection obtained through observation directly, photographing matters related to research and interview deeply on eleven informants. Data analyzed qualitatively consisting of three grooves activities that happen simultaneouslynamely reduction data, presentation of data and the withdrawal of a conclusion or data verification. The result of this research suggests that there are community members who the pros and cons with leadership the head of the village women, while methods of his leadership used sensitive to suggestions and use tipy misionary and developer type. While for obstacles faced the village head was the readiness of and willingness when needed by the local peopleup at any time. The solution offered to the village head in reducing the in leadership is to grow of the nature of trusted each other. When we do not capable of finised own, so finish by means of to distribute with the neares (deliberation ).